Income smoothing and underperformance in initial public offerings - Chaney, Paul K; Lewis, Craig M (Journal of Corporate Finance, 1998)
This paper investigates how firms that made initial public offerings of equity between 1975 and 1984 report earnings. For a sample of 489 firms, we find a positive association between a proxy for income smoothing and firm performance. That is, firms that perform well tend to report earnings with less variability relative to cash from operations compared to other firms. In addition, the five-year earnings response coefficient is greater for firms that are able to smooth earnings relative to cash flows. This result is consistent with a hypothesis that the market makes better assessments of the information content of earnings for firms with smoother earnings. Finally, we show that IPO firms tend to use discretionary accruals to smooth income relative to the prior year's earnings.